Analysis of Interfaith Marriage Arrangements in Islamic Family Law: Multiculturalism and Social Harmony Perspectives - Anam, Khoirul (Westscience Press, 2024)
This research aims to understand the analysis of Interfaith Marriage Arrangements in Islamic Family Law: Multiculturalism and Social Harmony Perspectives.Normative research is legal research that places law as a system of norms. The norm system itself is related to the principles, norms, rules of the legislation itself. The approach of examining statutory regulations aims to find out how consistent and appropriate the laws are with the legal problem or case being studied. Data collection techniques are a way of recording events or information, characteristics and all forms of information that describe the object of research. The results of research on interfaith marriages according to Islamic law as contained in the Word of Allah, Surah al-Baqarah verse 221, have confirmed that interfaith marriages are absolutely forbidden, apart from that, if you continue to carry out an interfaith marriage, many disputes will arise in the household because both partners have different opinions and beliefs. Interfaith marriage in Indonesia is a reality that continues to occur even though state law and religious law expressly prohibit it. In fact, if you look closely, Law no. 39 of 1999 concerning Human Rights in Indonesia does not explicitly regulate interfaith marriages. On the issue of more detailed marriage regulations, including the issue of interfaith marriages, Human Rights still returns it to the applicable laws and regulations, which in this case the Marriage Law in Indonesia is Law no. 1 in 1974.